Effect of ultrasonic vibration on ultra-precision diamond turning of Ti6Al4V - Pei, Lei; Wu, Hongbing (International journal of advanced manufacturing technology, 2019)
Because of the potential applications in the optical fields, the ultra-precision cutting of titanium alloys is attracting the interest of many researchers. Aimed at the problem of tool wear and poor surface quality in the ultra-precision cutting of titanium alloys, the method of ultrasonic vibration was used to assist the ultra-precision turning of titanium alloy for improving the machinability and better surface integrity. A lot of experiments of ultrasonic-assisted ultra-precision turning (UAUT) have been done to investigate the cutting phenomenon in UAUT of Ti6Al4V alloy. In addition, the effect of cutting parameters (amplitude of vibration, spindle speed, depth of cut and feeding speed) on the surface roughness, surface morphology, chip morphology and cutting force has been analyzed deeply. The results showed that the amplitude of ultrasonic vibration played the most important role in UAUT of Ti6Al4V alloy.